A Comparative Study of Fiscal Federalism in Nigeria, the United States of America and the United Kingdom - Stanley C. Duruibe; L. E. Akujuobi; Chidinma Nwabeke; Sampson Ogoke; Kate Emenalom (European Scientific Journal, ESJ, 2019)
The clamour for the adoption of ‘true fiscal federalism’ in Nigeria has been a burning issue in several quarters in the last three decades and has been documented in several articles, amongst which is the empirical study of Arowolo (2011:9). The United States of America (USA) which is the oldest federation in the world, and the United Kingdom– Nigeria’s erstwhile colonial master – were compared alongside Nigeria using qualitative comparative research method. This paper shows that these three countries have a lot of fascinating resemblance and conflicting ideals. For instance, although these three systems of fiscal federalism assign more powers to the central government, the manner in which the exercise these powers varies from one country to the other. Notably, while the Federal system of government in Nigeria exercises control over the natural resources of the devolved units, the devolved unit in the USA maintain control over their natural resources and remit returns to the centre; and in the UK mineral resources such as oil, gas, coal, gold and silver are controlled by the state while others are owned privately. The study, therefore, recommends amongst others that Nigeria should take a clue fromthe USA and UK system of resource control and fiscal federalism in order to foster national cohesion and promote sustainable growth and development among the federating units.